2006
DOI: 10.1002/acp.1216
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration inflation: how your ideas become mine

Abstract: Unconscious plagiarism occurs when individuals claim previously experienced ideas as their own. Using an adaptation of Brown and Murphy's (1989) three-stage paradigm, participant elaboration was investigated using the Alternate Uses Test at generation. Following generation, ideas were imagined and rated (imagery-elaboration), improved in three ways (generative-elaboration), improved by another participant and then imagined and rated (rich imagery-elaboration) or not re-presented. A week later, participants rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
24
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 27 publications
6
24
3
Order By: Relevance
“…Second, the responses given by each participant are much more distinctive and, so, memorable enough for the participants to avoid duplication. In our previous studies using the same generation tasks, we have also found minimal levels of initial plagiarism during the generation phase, although we did not previously report this (Stark & Perfect, 2006;Stark et al, 2005).…”
Section: Resultsmentioning
confidence: 49%
See 3 more Smart Citations
“…Second, the responses given by each participant are much more distinctive and, so, memorable enough for the participants to avoid duplication. In our previous studies using the same generation tasks, we have also found minimal levels of initial plagiarism during the generation phase, although we did not previously report this (Stark & Perfect, 2006;Stark et al, 2005).…”
Section: Resultsmentioning
confidence: 49%
“…However, in the recall-own task, plagiarism increased following generative elaboration, but not following imagery elaboration. In a series of follow-up studies, we have replicated this basic pattern (Stark & Perfect, 2006. Stark et al (2005) explained this pattern using a sourcemonitoring account (Johnson, Hashtroudi, & Lindsay, 1993).…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…What leads people to feel that they are remembering as opposed to thinking, fantasizing, etc.? As Jacoby and colleagues have pointed out, people can "retrieve" and use memory information from specific prior episodes without having the subjective experience of remembering (as in involuntary plagiarism; Stark & Perfect, 2006), and people can have the subjective experience of remembering specific prior episodes that they never, in fact, experienced (as in various forms of false memories; Jacoby et al, 1989). This "memory attribution" problem is equivalent to the sourcemonitoring problems described above; thoughts, images, and feelings that come to mind with characteristics typical of memories are likely to be experienced as memories, especially if the person is oriented to the past as a source of current mental events.…”
mentioning
confidence: 99%